A comparative experimental study of analgesic activity of a novel non-steroidal anti-inflammatory molecule – zaltoprofen, and a standard drug – piroxicam, using murine models - Santenna C (Journal of Experimental Pharmacology, 2019)
C Santenna, Sunil Kumar, S Balakrishnan, Ratinder Jhaj, Shah Newaz AhmedDepartment of Pharmacology, All India Institute of Medical Sciences Bhopal, Bhopal, Madhya Pradesh, IndiaPurpose: Pain is an unpleasant sensation, but a protective mechanism of our body. It is the most common medical complaint requiring a visit to a physician. The new non-steroidal anti-inflammatory drug (NSAID) – zaltoprofen, is a preferential COX-2 inhibitor. It also inhibits bradykinin-induced nociceptive responses by blocking the B2 receptor-mediated pathway in the primary sensory neurons. The present study was conducted to evaluate and compare the anti-nociceptive activity of zaltoprofen with a conventional NSAID – piroxicam, in a mouse model of acute pain using hot plate and tail flick tests.Materials and methods: Twenty-four adult Swiss albino mice (20–25 g) of either sex were used in this study. Oral zaltoprofen and piroxicam were used as test and standard drugs respectively. Anti-nociceptive activity was evaluated and compared using hot plate and tail flick tests.Results: In comparison to the control group (vehicle), zaltoprofen showed a significant increase in reaction time at various time periods in the hot plate and tail flick tests. In the hot plate method, zaltoprofen groups (15 and 20 mg/kg) showed a significant elevation in pain threshold in comparison to control group (vehicle) (p<0.001). In the tail flick model also, zaltoprofen groups (15 and 20 mg/kg) showed a significant increase in the reaction time in comparison to control group (vehicle). In both the analgesiometer assays, zaltoprofen was found to be non-inferior compared to a standard drug – piroxicam (positive control).Conclusion: Our study concludes that zaltoprofen is an effective analgesic agent in various pain models. Our results support that zaltoprofen has therapeutic potential for treating pain disorders and is non-inferior to a standard drug – piroxicam.Keywords: anti-nociceptive, hot plate, tail flick, zaltoprofen, piroxicam, mouse model